Method of Vortex Structure Identification in Axisymmetric Flow Field - Hyhlík, Tomáš (Manufacturing Technology Journal, 2015)
The article deals with the analysis of axisymmetric flow field from the point of view of vortex identification. The vortex is identified by using residual vorticity defined in the work [1]. The identification is based on the so called triple decomposition of motion [1]. The idea of vortex identification based on the residual vorticity which is easily applicable in the case of two dimensional flow field is extended to the case of axisymmetric flow. The analyses is based on the decomposition of velocity gradient tensor and on the search of so called basic reference frame which allows to examine clearly the kinematics of the flow field.
Keywords: Vortex Identification; Residual Vorticity; Tripple Decomposition; Axisymmetric Flow